2018
DOI: 10.1186/s40793-018-0311-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence of Planktotalea frisia type strain (SH6-1T), a representative of the Roseobacter group isolated from the North Sea during a phytoplankton bloom

Abstract: Planktotalea frisia SH6-1T Hahnke et al. (Int J Syst Evol Microbiol 62:1619–24, 2012) is a planktonic marine bacterium isolated during a phytoplankton bloom from the southern North Sea. It belongs to the Roseobacter group within the alphaproteobacterial family Rhodobacteraceae. Here we describe the draft genome sequence and annotation of the type strain SH6-1T. The genome comprises 4,106,736 bp and contains 4128 protein-coding and 38 RNA genes. The draft genome sequence provides evidence for at least three ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…2006, Bakenhus et al. 2018). In a study using metagenomic and metaproteomic approaches during phytoplankton blooms in the southern North Sea, metagenome assembled genomes (MAG) of Rhodobacterales members were recruited which showed that a distinct cluster affiliated to the Roseobacter group was closely correlated to the occurrence of distinct and dominant diatom species (Isaac et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2006, Bakenhus et al. 2018). In a study using metagenomic and metaproteomic approaches during phytoplankton blooms in the southern North Sea, metagenome assembled genomes (MAG) of Rhodobacterales members were recruited which showed that a distinct cluster affiliated to the Roseobacter group was closely correlated to the occurrence of distinct and dominant diatom species (Isaac et al.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the almost complete disappearance of the fucose-glycoconjugates in this treatment suggests that G. forsetii hydrolysed these threads making available the break down products to P. frisia. The genome sequences of P. frisia and G. forsetii revealed that this Roseobacter strain and Bacteroidetes members have the capability for both free-living and surface adhesion lifestyles (Bauer et al 2006, Bakenhus et al 2018. In a study using metagenomic and metaproteomic approaches during phytoplankton blooms in the southern North Sea, metagenome assembled genomes (MAG) of Rhodobacterales members were recruited which showed that a distinct cluster affiliated to the Roseobacter group was closely correlated to the occurrence of distinct and dominant diatom species (Isaac et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium was isolated during a phytoplankton bloom in the North Sea and constituted up to 0.4% of total bacterioplankton during phytoplankton blooms, predominantly as FL cells and as PA‐associated cells mainly during a Phaeocystis bloom but accounting only for a minor proportion (Hahnke, Brock, et al, 2013). The genome analysis of this strain indicated that it is able to switch between a FL and PA life style but no specific features of a PA life style were reported (Bakenhus et al, 2018). Hence, our observations are in line with these reports, underlining that this strain prefers a FL life style with only weak physical interactions with diatoms but affecting the life style of other bacteria (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, distinct bacteria, in particular members of Bacteroidetes, Gammaproteobacteria and the Roseobacter group, colonize and attach to the algal host cell, presumably enabled by encoded gene clusters for a tight attachment (Bauer et al 2006, de Bentzmann et al 2006, González et al 2008, Bakenhus et al 2018, Isaac et al 2021. These physical interactions between heterotrophic bacteria and phytoplankton species have received much attention in the recent past because they can affect the development of either or both partners negatively or positively with ecosystem-wide consequences (Li et al 2016, Cooper et al 2019.…”
Section: Introductionmentioning
confidence: 99%